Influência de parâmetros microestruturais na durabilidade de concretos leves produzidos com argila expandida - Weber Guadagnin Moravia (2007)
The low relation strength-weight of concrete, when compared to steel, constitutes a disadvantage of that material when applied in the construction. To improve this relation we can reduce the specific gravity of the concrete or increase its strength. Nowadays,lightweight concrete has been used in a larger scale for structural purposes and for reduction of the self weight of structures. However, one of the most importantrequirements of the concrete is that it should be durable under certain conditions of exposure, because in the last decades the number of concrete structures with some kind of deterioration has increased considerably, due to the exposure of those structures to an urban atmosphere. Few researches in this area study the durability oflightweight concrete. This work aims to evaluate the influence of the microstructural parameters of lightweight concrete using expanded clay as coarse aggregate in the durability of the material. There is a consensus in the literature indicating that the transition zone constitutes weak points in the structure of the concretes and more attention has been given to the influence of the transition zone between aggregate andthe cement matrix in several properties of the concrete. The durability of structural lightweight aggregate concrete (LWAC) was studied in comparison to normal-weight concrete (NWC) evaluating, mainly, thermal resistance, surface wearing, penetration of fluids and shrinkage. Assays of compressive strength, thermal conductivity, specific heat, thermal diffusivity, abrasion resistance and shrinkage were done to evaluate thedurability of the concretes. Chemical analysis, X-ray diffraction, scanning electron microscopy with microprobe analyzer (SEM-EDS), mercury intrusion porosimetry,pozolanic activity, and thermal analysis (TG), (DTG) and (DTA) were analyzed to study the microstructural parameters. The gotten results, had allowed predicting the influences of these parameters in the durability of the lightweight concrete and normalweight concrete. A transition zone denser and with better mechanics interconnectionswas observed between expanded clay and cement matrix in lightweight aggregate concrete (LWAC) than the existing between the limestone aggregate and cement matrix in normal-weight concrete (NWC). The lightweight concrete presented a better performance than normal-weight concrete when it durability was evaluated by assays which have a directly relation with the durability of the concretes.